Elementos constitucionais dos crimes contra a ordem econômica - Canuto Neto, Rubens de Mendonça (2024)
The objective of this work is to identify the elements of the Brazilian economic order, based on the Federal Constitution of 1988, and to demonstrate that its heterogeneous composition, formed from seemingly paradoxical elements, gives rise to a harmonious system that seeks to ensure a dignified existence for all, establishing a state of collective well-being. From this constitutional perspective, in which the end justifies the sacrifice of means, provided it is necessary, appropriate, and proportional to the goal to be achieved, Criminal Law is approached as a legal subsystem that integrally protects the economic order, encompassing all its elements, not just the cornerstone principles of free enterprise and free competition. Ultimately, elements from the Constitution are extracted that support a broader concept of crime against the economic order than that defined by the legislator.